EVALUASI KERENTANAN PERKOTAAN-DAS: PEMODELAN SPASIAL RISIKO BANJIR TERINTEGRASI DI KABUPATEN BANTAENG - Maula, Rahmatun; Qamal, Qanitatul Isra; Kamaruddin, Iqbal (Jurnal Spasial, 2026)
Flooding is a recurring hydrometeorological disaster in watershed areas characterized by diverse physical environmental conditions, including Bantaeng Regency, South Sulawesi, Indonesia. Variations in topography from upstream to downstream areas, slope gradient, soil type, geological conditions, rainfall, and land use patterns significantly influence flood vulnerability and risk. This study aims to spatially model integrated flood vulnerability and risk based on physical environmental and watershed characteristics in Bantaeng Regency. The research employs a Geographic Information System (GIS)-based approach using weighted overlay analysis of key physical parameters, including rainfall, slope, soil type, geology, elevation, and land use. Flood hazard and vulnerability were analyzed separately and subsequently integrated to produce flood risk maps. The results indicate that high to very high flood risk zones are predominantly concentrated in lowland and downstream watershed areas, particularly in regions with gentle slopes, fine-textured soils, and intensive built-up land use. Furthermore, the spatial analysis reveals that several road networks and public facilities are located within high-risk flood zones, potentially disrupting socio-economic activities. This study contributes to the development of integrated GIS-based flood risk modeling and provides essential insights to support regional planning, watershed management, and flood mitigation strategies at the local scale.